La Concordantia dei tre grandi sacramentari: Gregoriano, Veronese e Gelasiano - Sodi, Manlio; Baroffio, Giacomo; Toniolo, Alessandro (Saeculum Christianum. Pismo Historyczne, 2016)
The “tradition” of the Church always amazes us with its wealth and the characteristics of its documents. Also the liturgical tradition contributes in this in the important way. It is important to find the appropriate tools to learn about the same documents. In this way the great work done by the three scholars of liturgy is an example and reminder. Looking through all of the text reveals the infinity of elements which doubtless can be a great help per philolgiam ad theologia or ad culturam!